Online Polygamy or Virtual Bride: Cyber-Etnographic Research - Bati, Ugur; Atici, Bunyamin (Sage Publications Inc, 2011)
The developments that were experienced in the communication and technology area made Internet an important part of the daily life. In this respect, with the development of Internet, the changes in the social structure are closely connected with the lifestyles, attitudes, and behaviors of the people. In the study, the phenomena of virtual fellow wife and polygamy are researched and analyzed. A qualitative research, which is based on the observation fundamentally and richened with a survey and in-depth interviews, is carried out in accordance with the ethnographic research that is used in this study. The behavior-oriented observations are performed and the oral reports are arranged with the requirements that the research is performed in the natural environment. In the research, we see that two arguments such as I have been never remorseful because I am brought/I come as a fellow wife virtually'' and Bringing a fellow wife is not a question, it is our tradition'' showed the highest attitudes.
Keywords: virtual; polygamy; etnographic study; Turkey